(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Pushing forward public hospital reform and optimising the medical service system has become the top objective of Uzbekistan’s new medical reform, as the country’s society continues to expand and people’s living standards rise. Meanwhile, the guiding principles of the medical reform have shifted to include public hospitals as the front-runners in the healthcare system, encouraging the concurrent development of non-public hospitals, and maintaining non-profit hospitals as the core of the healthcare system with for-profit hospitals serving as supplements. The competition amongst hospitals has increased as a result of this shift in guiding principles. Hospitals are putting a lot of emphasis on cutting costs and raising service standards in order to compete.